The Longest day [videorecording] - Annakin, Ken; Marton, Andrew; Wicki, Bernhard; Williams, Elmo (Twentieth Century Fox, 1962)
The complete story of the D-day landings at Normandy, as seen through the ages of American, French, British and German participants.